Legal Protection of Traditional Music Performances in Indonesia’s Tourism Sector: Lessons from the Philippines and Malaysia - Lu Sudirman; Fernando Fernando; Hari Sutra Disemadi; Nur Ezan; David Tan (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
This study addresses the growing utilization of traditional music performances as a tourism attraction, which simultaneously raises legal concerns, including unauthorized commercialization, lack of clarity in royalty arrangements and benefit-sharing, and risks of misuse through recording and digital promotion. These conditions reflect a gap between the normative recognition of traditional music and its practical implementation within the tourism sector. This research aims to compare the legal frameworks in Indonesia, the Philippines, and Malaysia, and to formulate an ideal regulatory model for Indonesia in protecting traditional music performances in tourism. The method employed is normative legal research using statutory and comparative approaches. The findings indicate that Indonesia emphasizes state custodianship over Traditional Cultural Expressions (TCEs), the Philippines prioritizes recognition of indigenous communal rights, cultural registration, and institutional strengthening, while Malaysia adopts a more operational regulatory framework concerning performers’ rights, remuneration, and the commercial use of performances. An ideal regulatory framework for Indonesia should be directed toward the classification of utilization permits, strengthening the role of custodian communities, identifying primary commercial users, regulating benefit-sharing mechanisms, establishing standard contractual provisions, monitoring digital use, and enhancing cross-sectoral coordination to ensure greater legal certainty and fairness in protecting traditional music performances.